Measuring class teacher's perceptions of revised parental involvement scale - Arivayagan, Keetanjaly; Abdul Kadir, Suhaida; Wong, Su Luan; Abdullah, Arnida (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
This study aims to validate an integrative Parental Involvement scale based on theory and parental involvement research using rigorous scale validation procedures. An adapted questionnaire with 20 items was administered to 506 secondary class teachers to measure their perceptions towards facilitating parental involvement in secondary schools. Data were examined by performing exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using SPSS 23.0 and AMOS 23.0 software, respectively. The findings supported Parental Involvement as a multidimensional construct with its three underlying dimensions: school-home interaction, school-based involvement, and home-based involvement. Only a handful of research-based studies probed into Parental Involvement scale as a multi-dimensional construct in secondary schools within the Malaysian context. Therefore, a validated Parental Involvement scale with 15 items measures the nature of parental involvement in secondary schools, which can be proposed to be used as an evaluative tool for schools that are interested in assessing parental involvement and the effects of various programs, such as SARANA Sekolah, that target the three dimensions of parental involvement measured. The Parental Involvement scale would also foster the identified factors that influence the role of parents in schools and school effectiveness. The practical implications, methodological limitations, and future recommendations are discussed.